Jorge el curioso y el conejito - Rey, H. A. (Hans Augusto), 1898-; Rey, Margret; Canetti, Yanitzia, 1967- (Boston, Mass. : Houghton Mifflin, 2002)
When George the monkey finds a hutch full of bunnies and wonders what it would feel like to hold one, he creates a serious problem for himself.
Cover title.
On board pages.
Translation of: Curious George and the bunny
Based on: Curious George flies a kite
Keywords: Monkeys -- Fiction; Rabbits -- Fiction; Spanish language materials